High Expectations: How Tourists Cope With Disappointing Vacation Experiences. (May 2023) - Hossain, Muhammad Ismail; Oppewal, Harmen; Tojib, Dewi
This study investigates how expectations, locus attribution and disappointment determine coping behaviors when tourists encounter a negative vacation experience. Drawing upon cognitive appraisal theory, it is first hypothesized that individuals with high expectations are more likely to engage in coping behaviors than individuals with low expectations. Disappointment mediates this relationship. Next it is hypothesized that locus attribution of the negative experience moderates these effects. Results from two scenario-based experiments support the hypotheses. Specifically, attribution has a greater effect on disappointment when the provider is the locus instead of the situation. This is particularly so when expectations are low. Greater amounts of confrontative than support-seeking coping result when expectations are high and the provider is the locus. Instead, there is no difference in coping when expectations are low. These findings suggest that tourist services can influence disappointment and related coping behaviors by managing not only tourists' expectations but also tourists' attributions.